New Media and Children Internet Content Preferences of Primary School Children in Turkey - Atici, Bunyamin; Bati, Ugur (Kassel Univ Press Gmbh, 2010)
As the technology develops and expands, computers have a very significant role in the world of children. The aim of this survey is to study the internet habits of 6-13 age groups of children. Moreover, we will deal with how they utilize the new media tools in Turkey. A questionnaire is prepared content with this research and is applied on 366 participants from various regions of Turkey. Sampling of the research consists of 366 children of 6-13 age groups. The research data are analyzed in the program of SPSS 10.0 in the frequency and chi square test analysis. The results of the field survey reveals: 61,9 % of children have internet access at home. In addition, 95,8 % of the children are internet users. 49,1 % of the children are in the internet to play games, 26 % of them to communicate with friends and only 6,0 % of the children use internet to do homework.
Keywords: Technology; internet; new media; primary school children; social networks